(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Workplace ostracism is a form of silent mistreatment where an individual experiences deliberate denied social interaction with others. It is believed to be a universal phenomenon which silently injures the human heart. Ostracism is believed to be very destructive as the ostracized person finds it difficult to prove that he is being ostracized due to its covert nature. It is a proven fact that the nature of mistreatment under ostracism can be silent but its outcomes in the form of decreased job engagement, diminished work performance, increased intention to quit, etc. are very vocal. The relationship between workplace ostracism and its negative consequences is explained in the light of Conservation of Resources theory. According to conservation of resources theory, every individual is attached to various kinds of resources which they perceive as worthy. The theory claimed that when an individual encounters resource loss or is threatened of potential loss, such experiences disturbs his psychological well-being. This study also describes the coping mechanism which an individual can adopt in order to manage the negative aspects of workplace ostracism. The organizational administrators need to focus on this silent form of harassment, which is making the organization weak on a broader scope. Thus, a serious need of encouraging healthy communication, cooperation and coordination is required in every organization in order to avoid counter-productive work behaviors.